Access Bridge Design Measures for Safety Increase of the Road Infrastructure - Micunek, Tomas; Schejbalova, Zuzana; Schmidt, Drahomir (Promet - Traffic&Transportation, 2013)
Solid barriers represent danger for the driver in case of traffic lane escape. This threat can be represented by a drainage ditch culvert face. The access bridge is not usually conspicuous enough near the traffic lane so that the driver could ditch and crash this barrier in case of an exceptional situation such as avoidance manoeuvres. This work deals with a technical solution of access bridges with an integrated deformation zone which was designed on the ground of a detailed analysis of current types of the construction. The new technical solution was proved by means of a numerical simulation of passenger car impact and compared with the current design of culvert faces.